2022
DOI: 10.1111/nyas.14753
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA circ_0001459 accelerates hepatocellular carcinoma progression via the miR‐6165/IGF1R axis

Abstract: An increasing amount of evidence shows that circular RNAs (circRNAs) have critical effects on cancer progression and development; however, the biological function and potential molecular mechanism of circRNAs in hepatocellular carcinoma (HCC) are still unclear. CircRNA sequencing was used to identify differentially expressed circRNAs between HCC tissue and adjacent normal tissue. We found that circ_0001459 expression was significantly elevated in HCC tissue and cell lines. Furthermore, in vitro and in vivo fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…Dual-luciferase reporter assays confirmed the interaction between has_circ_0001459 and miR-6165, as well as between miR-6165 and IGF-1R. This confirmed that has_circ_0001459 can sponge miR-6165 and induce upregulation of its downstream target IGF-1R, thereby promoting invasion, migration, and EMT of HCC cells and significantly advancing the progression of HCC [30] . This suggests that has_circ_0001459 may serve as a prognostic factor and therapeutic target in hepatocellular carcinoma.…”
Section: Has_circ_0001459 (Circneil3)supporting
confidence: 55%
“…Dual-luciferase reporter assays confirmed the interaction between has_circ_0001459 and miR-6165, as well as between miR-6165 and IGF-1R. This confirmed that has_circ_0001459 can sponge miR-6165 and induce upregulation of its downstream target IGF-1R, thereby promoting invasion, migration, and EMT of HCC cells and significantly advancing the progression of HCC [30] . This suggests that has_circ_0001459 may serve as a prognostic factor and therapeutic target in hepatocellular carcinoma.…”
Section: Has_circ_0001459 (Circneil3)supporting
confidence: 55%
“…In contrast, six circRNAs, circ_0003998 ( Song et al, 2020 ), circ_0101145 ( Jin et al, 2020 ), circBACH1 ( Li et al, 2021 ), circPUM1 ( Zhang et al, 2021 ), circ_0051040 ( Ju et al, 2022 ) and circ_0001459 ( Shen et al, 2022 ), have been observed to manipulate various miR/mRNA axes to induce EMT. Besides, elevated level of circSEC24A leads to the expression of protein phosphatase, Mg2+/Mn2+ dependent 1F (PPM1F) and matrix metalloproteinase 3 (MMP3) by sponging miR-455-3p and miR-421, respectively ( Liao et al, 2021 ; Zhang and Zhou, 2022 ).…”
Section: Emt-related Ncrnas Mechanisms Of Actionmentioning
confidence: 97%
“…Circ000149 (Figure 1) was increased in patients with HCC and promoted growth, migration, and invasion of HepG2 and Huh7 HCC cells (26). Circ0001459 promoted tumor growth and lung metastasis of these cell lines after injection into the flanks of nude mice (26). Circ0001459 sponged miR-6165 and up-regulated IGF-1R (26).…”
Section: Circrnas Up-regulating Transmembrane Receptorsmentioning
confidence: 99%